Cyberbullying in the Digital Era: A Systematic Review from a Technology Psychology Perspective - Ghina Nisrina; Nazira Irsyani; Pinkan Meilani; Konto Iskandar Dinata (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Cyberbullying has emerged as a significant psychosocial phenomenon in the digital era, causing serious psychological impacts on victims. This study aims to conduct a systematic review of current literature on cyberbullying from a technology psychology perspective, identifying forms of cyberbullying, psychological impacts, and digital-based interventions. The systematic review was conducted using SCOPUS, PubMed, PsycINFO, and Google Scholar databases for the 2019-2024 period with keywords including